Inhibition of hypoxia-inducible factor-1alpha (HIF-1alpha) protein synthesis by DNA damage inducing agents. - Jessica Jie Wei Lou; Yee Liu Chua; Eng Hui Chew; Jie Gao; Martin Bushell; Thilo Hagen (PLoS ONE, 2010)
Hypoxia-inducible factor (HIF) is a heterodimeric transcription factor that is composed of a hypoxia-inducible alpha subunit (HIF-1alpha and HIF-2alpha) and a constitutively expressed beta subunit (HIF-1beta). HIF mediates the adaptation of cells and tissues to low oxygen concentrations. It also plays an important role in tumorigenesis and constitutes an important therapeutic target in anti-tumor therapy. We have screened a number of reported HIF inhibitors for their effects on HIF-transcriptional activity and found that the DNA damage inducing agents camptothecin and mitomycin C produced the most robust effects. Camptothecin is a reported inhibitor of HIF-1alpha translation, while mitomycin C has been reported to induce p53-dependent HIF-1alpha degradation. In this study we demonstrate that the inhibitory effect of mitomycin C on HIF-1alpha protein expression is not dependent on p53 and protein degradation, but also involves HIF-1alpha translational regulation. Initiation of a DNA damage response with the small molecule p53 activator NSC-652287 (RITA) has been reported to inhibit HIF-1alpha protein synthesis by increasing the phosphorylation of eIF2alpha. However, we show here that even when eIF2alpha phosphorylation is prevented, the DNA damage inducing drugs mitomycin C, camptothecin and NSC-652287 still inhibit HIF-1alpha protein synthesis to the same extent. The inhibitory effects of camptothecin on HIF-1alpha expression but not that of mitomycin C and NSC-652287 were dependent on cyclin-dependent kinase activity. In conclusion, specific types of DNA damage can bring about selective inhibition of HIF-1alpha protein synthesis. Further characterization of the involved mechanisms may reveal important novel therapeutic targets.